Redescription and DNA barcoding of diurnal moth Athroolopha latimargoRothschild, 1914 bona sp., stat. rev. from the southern Iberian Peninsula (Lepidoptera: Geometridae: Ennominae) - Guerrero, Juan J.; Cuenca, E. David; Barros, David; Ortiz, Antonio S. (Zootaxa, 2020)
The rare and diurnal geometrid moth Athroolopha latimargo Rothschild, 1914 bona sp., stat. rev. is re-discovered and redescribed from the furthest point of the south of the Iberian Peninsula, for the first time since its original description as a subspecies of Athroolopha chrysitaria (Hübner, 1813) from North Africa. The range of this taxon is questioned. A mitochondrial COI barcode sequence was generated for the specimens and compared with Iberian and Sicilian Athroolopha species.